Determination S-Parameters of PTFE at X-BandFrequency using FEM modeling rectangular waveguide - Soleimani, Hassan; Abbas, Zulkifly; Khalid, Kaida; Yahya, Noorhana; Soleimani, Hojatollah (EuroJournals, 2010)
In this paper the simulation of distribution electric field intensity of polytetrafluoroethylene (PTFE) sample placed in rectangular waveguide based on FiniteElement Method (FEM) are investigated to show the essential differences of radiatedelectric field intensity. The computations of S-parameters of samples were determined byimplementation FEM modeling.